CONDUIT MODELING OF MAGMA FLOW DYNAMICS: A CASE STUDY ON THE ERUPTIVE PROCESS AT THE TIANCHI VOLCANO - Wei H.Q.; Melnik O.; Barmin A.; Liu Y.S.; Sparks R.S.J. (My University, 2006)
Magma uprising velocity is related to the viscosity, density and pressure of the magma, in the lower part of conduit, and a usual model of a viscous liquid can be applied to simulate the flow dynamics of magma. In the intermediate zone, equations of mass conservation for liquid and gas phases transformation and equation of momentum for the mixture as a whole can be used while Darsy law is used for the gas phase nucleation and growing process. Equations of mass conservations for the gas, accounting for free gas and gas in large particles, and equations of momentum for components of the mixture are used for the upper fragmented part of the conduit. There is 3% bubble volume in the chamber when the Millennium eruption maintained a plinian column from a 62 m diameter conduit. The magma become fragments when the bubble volume reached to 65 % and expelled out of the vent in 145 ms-1, a gas velocity of 170 ms-1 and a gas-particle dispersion exit pressure of 12.2MPa. Bubble volume in the magma chamber increased as high as 30% ~ 40% before the caldera collapsed, which led to 70% ~ 75% fragmented bubble volume, 180 ms-1 gas exit velocity and 7 ~ 8MPa exit pressure. Qixiangzhan parasitic eruption is represented by weak explosive activity, from a 40 m diameter conduit, with gas exit velocity 15 ~ 25 ms-1 and extrusive eruptions. Porosity of the pumices in this case is lower than for Millennium eruption, 48% to 61% and pumice density is higher, 1.01 ~ 1.35g cm-3. During the extrusive phase peak discharge rate could reach up to 42 m3s-1 (DRE) and porosity varies in the range of 70% ~ 80%.
Keywords: CONDUIT DYNAMIC MODELING; MILLENNIUM ERUPTION; PARASITIC ERUPTION; TIANCHI VOLCANO